2020
DOI: 10.1017/s0007114520000379
|View full text |Cite
|
Sign up to set email alerts
|

Abomasally infused SFA with varying chain length differently affect milk production and composition and alter hepatic and mammary gene expression in lactating cows

Abstract: The aim of the present study was to compare the effects of post-ruminally infused fat supplements, varying in fatty acid (FA) chain length, on animal performance, metabolism and milk FA. Eleven multiparous Holstein dairy cows were used in a replicated incomplete 3 × 3 Latin square design with 7-d periods, separated by 7-d washouts. Treatments were administered as abomasal infusions of enrichments providing 280 g/d of FA: (1) palmitic acid (98·4 % 16 : 0; PA), (2) caprylic and capric acids (56·2 % 8 : 0, 43·8 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The apparent digestibility of FA in our study was found to be well within the range of previously reported estimates in ruminants (Andrews and Lewis 1970;Rico et al, 2017Rico et al, , 2020. Comparability across studies may be limited by methodological differences, such as FA feeding level and method of delivery, as well as by species-related differences (Steele and Moore, 1968;Boerman et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The apparent digestibility of FA in our study was found to be well within the range of previously reported estimates in ruminants (Andrews and Lewis 1970;Rico et al, 2017Rico et al, , 2020. Comparability across studies may be limited by methodological differences, such as FA feeding level and method of delivery, as well as by species-related differences (Steele and Moore, 1968;Boerman et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Some of the major factors influencing FA digestibility include the dietary FA load, FA matrix (e.g., whole seeds vs. calcium salts), degree of esterification (i.e., free FA vs. triglyceride), degree of saturation (i.e., unsaturated vs. saturated), and carbon chain length (Andrews and Lewis, 1970;Palmquist, 1991;de Souza and Lock, 2019). Compared with UFA, the digestibility and absorbability of long-chain SFA are generally limited (Andrews and Lewis, 1970;Pantoja et al, 1996;Rico et al, 2020) because of higher melting points relative to FA with shorter carbon chains (Steele and Moore, 1968). Although the diet of dairy cows is mostly composed of 18-carbon (18C) PUFA, extensive rumen hydrogenation dictates that the majority of FA reaching the small intestine are SFA (Doreau and Ferlay, 1994), and the duodenal flow of FA is high in stearic acid (18:0), at rates commonly exceeding 500 g/d (Lock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ACACAα PII, the expression of FASN was not affected by SA relative to Control and seemed to counter the effects of CLA in the CLASA treatment. Rico et al (29) reported no effect of abomasal infusions of C18:0 on ACACAα and FASN gene expression in dairy cows. Further, the mRNA abundance of PPAR-γ, a key transcription factor for lipogenic genes, was increased by the SA treatment, which suggests that this saturated FA is a natural agonist for PPAR-γ.…”
Section: Discussionmentioning
confidence: 99%
“…The minor effect on the transcription of the RT-qPCR measured putative PPAR target genes in the PCLS treated with the various PPAR agonists may indicate poor response of the liver to PPAR agonist. This is a possibility, considering the poor response observed in prior studies using in vivo supplementation of C16:0 on liver transcriptome ( 16 , 44 , 45 ) or the lack of response on P450 enzyme activity to the PPARα agonist Wy-14643 in goats ( 46 ). This possibility would be a major obstacle for any nutrigenomic interventions to improve liver performance in dairy cows via activation of PPAR, as previously advocated ( 13 ).…”
Section: Discussionmentioning
confidence: 99%